2005
DOI: 10.1103/physrevb.71.094426
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of density of states near the Fermi level in a strain-free epitaxial film of the hole-doped manganiteLa0.7Ca0.3MnO3

Abstract: Scanning tunneling spectroscopy measurements were performed on an epitaxial thin film of La 0.7 Ca 0.3 MnO 3 grown on a NdGaO 3 substrate. The temperature variation of the density of states ͑DOS͒ close to the ferromagnetic transition temperature ͑T c ͒ was investigated. The strain-free film exhibiting a sharp metal-insulator transition at T p Ϸ T c Ϸ 268 K shows no phase separation as seen by the conductivity map, allowing unambiguous determination of the tunneling spectra as a function of T. The temperature d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 27 publications
6
28
0
Order By: Relevance
“…From Figure 3(a) it is clear that the tunneling current at higher bias voltage has a minimum value between 100 K and 120 K. The three I(V) spectra presented in Figure 3(b) confirm this observation, with the dashed curve recorded at 106 K showing a significantly lower current at high tunneling biases. A similar temperature dependence of the I(V) curves near the metal-insulator transition temperature (T MIT ) was also observed by others on related La 0.7 Ca 0.3 MnO 3 films 36 . Following the reasoning in this work we conclude this high-bias minimum is a signature of a metal-insulator phase transition in the surface DOS of our oxygen deficient LPCMO films.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…From Figure 3(a) it is clear that the tunneling current at higher bias voltage has a minimum value between 100 K and 120 K. The three I(V) spectra presented in Figure 3(b) confirm this observation, with the dashed curve recorded at 106 K showing a significantly lower current at high tunneling biases. A similar temperature dependence of the I(V) curves near the metal-insulator transition temperature (T MIT ) was also observed by others on related La 0.7 Ca 0.3 MnO 3 films 36 . Following the reasoning in this work we conclude this high-bias minimum is a signature of a metal-insulator phase transition in the surface DOS of our oxygen deficient LPCMO films.…”
Section: Resultssupporting
confidence: 85%
“…The increase in ZBC above the T MIT is consistent with that observed in La 0.7 Ca 0.3 MnO 3 36 , where it was attributed to thermal broadening of the spectroscopic data in the presence of a small polaronic gap, see Refs. 36,38 and the discussion below. Clearly a zero-field temperature dependent MIT is present at the surface of oxygen-deficient, insulating, 3D perovskite LPCMO films with a Mn-O termination.…”
Section: (B) Three Selected I(v) Curves Above (238k) Near (106k) Anmentioning
confidence: 98%
See 1 more Smart Citation
“…The presence of these micrometric particles in the initial stages of growth of the nanolayers may bring about an accumulative effect of defects on the final surface of the film, thus causing an accelerated increase in the roughness. In addition, it was suggested that the film roughness is influenced by strain induced in the film by a lattice mismatch with the substrate [19], this affect the roughness both ablation regimens. Figure 6 shows images obtained by scanning electron microscopy (SEM) of the films grown with 6000 and 12,000 shots, with a single-pulse and multi-pulse regime, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The substrates were chosen because of their small lattice mismatch ͑about 0.3%͒ with the bulk LCMO, which ensures minimized strain in the resulting films to prevent excess strain-induced effects on the electronic properties. 21,22,34 The films were deposited in a 100 mTorr oxygen background pressure to a thickness of ͑110Ϯ 10͒ nm with the substrate temperature kept at 650°C, and were subsequently annealed at the same temperature for 2 h in 100 Torr O 2 and then cooled slowly to room temperature. The epitaxy of these films was confirmed by x-ray diffraction, and the film quality was further verified by atomic force microscopy and STM measurements, showing terraced growth with step heights corresponding to one c-axis lattice constant of the bulk LCMO, as exemplified in Fig.…”
Section: Methodsmentioning
confidence: 99%